Social media and collective identity on protest, analysis comparative of Omnibus Law protest and Hongkong 19-20 protest - Sutan, Arissy Jorgi (Masyarakat, Kebudayaan dan Politik, 2024)
The large protests against the New Amendment to the Extradition Bill in Hong Kong and the Omnibus Law 2020 Job Creation Bill in Indonesia are proof of the massive public movement through social media. This study aims to determine how social media is used in social movements in terms of dichotomy content, actor clusters, and collective identity formation in two cases: Indonesia (Rejection of the Omnibus Law Job Creation Bill) and Hong Kong (Rejection of the Extradition Bill Amendment). Differences and similarities are listed below. This research uses a Qualitative Method, with the analysis using Qualitative Data Analysis Software (Q-DAS), namely NVIVO 12Plus. This study has the following results: First, the dichotomy content between Indonesia and Hong Kong tends to be evenly distributed. Second, both examples show parallels in the distribution of actor clusters with the dichotomy, demonstrating that both cases have become a significant movement. Third, the collective identity in the Indonesian case refers to the contesting parties in the pros and cons of the Omnibus Law. In contrast, the Hong Kong case relates to protecting the Hong Kong people’s ethnicity, language, politics, economy, and culture. The limitations of this study focus on social media in social movements and collective identities, excluding regulatory analysis and aspects of digital/mass media. This study recommends further research focusing on the legal consequences of the Omnibus Law and including digital and mass media in the framing of social movements.